Barroso MGT, Vieira NFC, Varela ZM. Health education: in the context of human development. Fortaleza: Democritus editions Rock, 2003 120p. - Castro, Maria Euridéa de (Rev Rene, 2006)
For timely comments is a publication thatsuggests innovative proposals on Health Education, with the organizers Maria GrasielaTeixeira Barroso, Neiva Francenely C. Vieira,Zulene Maria V. Varela that anguished with the slowness of the changes that would occurin the areas Education and Health, lead the process of health education in undergraduatecourses, Masters and PhD within an innovative model, offering alternative proposals to the current models.